FLASH radiotherapy at a crossroads: a bibliometric perspective on progress and challenges - Wang, Peng; Gao, Yu-Geng; Chen, Can; Zhao, Xiaoxin; Zhang, Yuying; Liu, Taorui; Jiang, Haoran; Wang, Zhe; Zhao, Xiang; Li, Jianjun (Discover oncology, 2025)
Flash radiotherapy (FLASH-RT), an emerging modality utilizing ultra-high dose-rate (UHDR) irradiation (typically > 40 Gy/s), has demonstrated a unique capacity to preserve normal tissue integrity while maintaining tumor control efficacy compared to conventional radiotherapy. Despite exponential growth in FLASH-RT research over the past decade, its scientific landscape has not yet been systematically characterized through bibliometric analysis. This study only includes articles from the Web of Science Core Collection (WoSCC) and is limited to English-language publications, which may introduce database and language biases.
Online veröffentlicht: 17. August 2025
Gesehen am 10.11.2025